Axonal transport and localization of B-50/GAP-43-like immunoreactivity in regenerating sciatic and facial nerves of the rat - Tetzlaff, W (J Neurosci, 1989)
Neurons that can regenerate their axons following axotomy increase their synthesis and axonal transport of a growth-associated protein, called GAP-43, which has been shown to be identical to the synaptic phosphoprotein B-50. The function of B-50/GAP-43 to the process of regeneration is unknown. We used a polyclonal, affinity-purified antibody against B-50 to study the axonal transport and localization of B-50/GAP-43-like immunoreactivity (B50LI) in the regenerating sciatic and facial nerves of adult rats. Quantitative data were obtained by densitometry of the B-50 band in immunoblots of nerve segments, which had been run on SDS-polyacrylamide gels. In the regenerating sciatic nerve, anterograde accumulation at a collection ligature was 3.0 times higher than retrograde accumulation. The mobile fraction of B50LI was only 0.28 of total B50LI and traveled with a mean anterograde velocity of 5.3 mm/hr. B50LI distribution in the newly regenerated portion of the nerve revealed maximal B50LI levels midway between the position of the crush and the fastest-growing axons. Immunocytochemistry of this portion of the nerve demonstrated B50LI to be associated with regenerating axons but also to a large extent with extra-axonal structures outlining the Schwann cell bands of Bungner. This zone of B50LI-positive Schwann cell bands was found to extend more distally in nerves in which regeneration had processed longer, e.g., up to 5 mm distal to the crush after 3 d and 8 mm after 4 d. Further distal to this zone, many fine regenerating axonal profiles could be detected with B-50 antibody, but were neurofilament negative. These findings raise the possibility of an extra-axonal function of B-50/GAP-43, as this protein might be secreted from regenerating axons and might play a role in axon-Schwann cell interactions during axonal maturation.